2022
DOI: 10.3390/min12091089
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Speciation of Rare Earth Elements in Coal Fly Ash from the Qianxi Power Plant, Guizhou Province, Southwest China

Abstract: Coal fly ash (CFA), hazardous to the environment and human health, has been considered to be a potential alternative source for rare earth elements (REEs) in recent years. However, information on how REEs distribute and occur in coal fly ash is still incomplete. In this work, particle size analysis, inductively coupled plasma–mass spectrometry, scanning electron microscopy, and electron probe microanalysis were applied to study the occurrence and distribution of REEs in a fly ash sample from the Qianxi coal-fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…Franus et al 7 reported 500–600 mg kg −1 of total REEs in some Polish fly ash, a similar concentration (630 mg kg −1 ) was reported by Wu et al 8 for a fly ash sample from the Guizhou province of China. Blissett et al 9 compared six fly ash samples from the UK and Poland, and found that the concentration of REEs varied from 246 to 481 mg kg −1 .…”
Section: Introductionsupporting
confidence: 75%
“…Franus et al 7 reported 500–600 mg kg −1 of total REEs in some Polish fly ash, a similar concentration (630 mg kg −1 ) was reported by Wu et al 8 for a fly ash sample from the Guizhou province of China. Blissett et al 9 compared six fly ash samples from the UK and Poland, and found that the concentration of REEs varied from 246 to 481 mg kg −1 .…”
Section: Introductionsupporting
confidence: 75%
“…Table 4 presents the potential of these alternative REE resources. A big country like China uses about 4 billion tons of coal for its power plants to generate electricity which produces about 500-550 million tons of fly ash [85]. Coal and coal combustion products such as fly ash, bottom ash, and incinerator ash are found to contain significant amounts of REE as most coal samples contain minor amounts of rhabdophane, Nd, Ce, La (PO4).H2O, monazite, (Ce, La, Th, Nd)PO4, and xenotime (Y, Er)PO4 [86].…”
Section: Coal Coal Fly Ash and Related Materialsmentioning
confidence: 99%
“…Coal fly ash (CFA), a byproduct of coal burning in thermal power plants, has recently gained attention as a potential resource for REYs [ 9 , 10 , 11 ]. While challenges exist regarding low concentrations and extraction complexities since REYs are encapsulated within glassy particles [ 12 ], ongoing research and technological advancements are making it increasingly feasible to recover REYs from this unconventional source [ 13 ]. Further, this could contribute to more sustainable REY supply chains.…”
Section: Introductionmentioning
confidence: 99%
“…However, CFA poses a severe risk to both the environment [ 14 , 15 , 16 ] and human health due to its composition and potential for leaching [ 17 , 18 , 19 , 20 , 21 ] and dispersion [ 22 , 23 , 24 ]. The danger from CFA arises from the presence of various toxic substances, particularly heavy metal(loid)s (HMs), including As, Pb, Hg, Cd, Cr, and Ni [ 12 , 25 ]. These HMs are naturally present in coal and become concentrated in the ash during combustion.…”
Section: Introductionmentioning
confidence: 99%